EKSISTENSI RAKYU DALAM PENGEMBANGAN HUKUM ISLAM - Ismail Ismail (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Ijtihad which has evolved since the era of Khulafa` al-Rasyidin has outlined positive values in determining the law at the time of the passage of al-Qur`an and Sunnah do not determine the law explicitly. In this condition rakyu is necessary to avoid a gap in legal when needed. The Prophet permission to use rakyu also identifies that the legal provisions explicitly limited while law events are always evolve following future developments. This is where ijtihad has a very important role in the development of Islamic law. The role of ijtihad here is looking for appropriate and relevant legal alternatives for the situation and the conditions in which ijtihad was done, especially when linked to the current condition that is far different from the situation at the time of the revelation (Wahyu) revealed. Nevertheless, the use of rakyu must be done by using the clear signs and do not follow the passions, such as the stance taken by the mujtahid from previous generations. The use of rakyu in performing law istibath undoubtedly has contributed significantly in the development of Islamic law.